Determinants of Group Loans Uptake at The Youth Enterprise Development Fund - Kilele, Andrew K.; Nduruhu, David; Kimani, Maina E. (My University, 2015)
The Government of Kenya has established the Youth Enterprise Development Fund and other Government Funds to help reduce unemployment rate among the youth. Despite this effort by the government, the uptake of these funds remains low. The study intended to f ind out the determinants of group loans uptake at the Youth Enterprises Fund in Nakuru West Constituency. The accessible population was drawn from the registered youth groups in Nakuru West Constituency which are 520 in number. Primary data was collected by use of structured questionnaires. Data was analyzed using both descriptive statistics and inferential statistics. SPSS was used to process and analyze the data. According to the findings, lending procedures and policy was found to have the most significant effect on the group loan uptake while financial literacy training had the least effect on loan uptake. It was recommended that the management of the Youth Enterprise Development Fund should come up with appropriate means to reach and communicate to the youths; start up loan amount should be increased so should the loan repayment period; the management should also come up with suitable lending procedures and policy that are friendly to the youths and finally youths should be trained on financial literacy so as to increase group loans uptake at the Youth Enterprise Development Fund.
A Survey of Nakuru West Constituency, Kenya
Keywords: Group Loans Uptake; Youth Enterprise Development Fund; Lending Procedures; Financial Literacy